CREATIVITY IN ENGLISH CLASSES IN HIGHER EDUCATION INSTITUTIONS (Modern education and development, 2024)
The development of creativity in English language classes at higher education institutions can provide students with valuable experience and skills. This article discusses the importance of creativity not only in language learning but also in overall personal and professional development.Развитие креативности на занятиях по английскому языку в высших учебных заведениях может обеспечить студентам важный опыт и навыки. В этой статье говорится о важности креативности не только в изучении языка, но и в общем личностном и профессиональном развитии.